Fluorescent sensing platform for low-cost detection of Cu2+ by coumarin derivative: DFT calculation and practical application in herbal and black tea samples - Savran, Tahir; Karagoz, Abdurrahman; Karuk Elmas, Sukriye Nihan; Aydin, Duygu; Ozen, Furkan; Koran, Kenan; Yilmaz, Ibrahim (Tubitak Scientific & Technological Research Council Turkey, 2020)
A fluorogenic probe based on a coumarin-derivative for Cu2+ sensing in CH3CN/H2O media (v/v, 95/5, 5.0 mu M) was developed and applied in real samples. 3-(4-chlorophenyl)-6,7-dihydroxy-coumarin (MCPC) probe was obtained by synthetic methodologies and identified by spectral techniques. The probe MCPC showed remarkable changes with a turn-off fluorogenic sensing approach for the monitoring of Cu2+ at 456 nm under an excitation wavelength of 366 nm. The response time of the probe MCPC was founded as only 1 min The detection limit of the probe MCPC was recorded to be 1.47 nM. The binding constant and possible stoichiometric ratio (1:1) values were determined by Benesi-Hildebrand and Job's plot systems, respectively. The mechanism of the probe MCPC with Cu2+ was further confirmed by ESI-MS and FT-IR analyses, as well as supported by theoretical calculations. Furthermore, the probe MCPC was successfully employed for the practical applications to sense Cu2+ in different herbal and black tea samples. The proposed sensing method was also verified by ICP-OES method.
Keywords: Coumarin; fluorescent sensor; copper; DFT; tea samples